Prevalence of depression and anxiety among university students in Jeddah, Saudi Arabia: exploring sociodemographic and associated factors - Malebari, Azizah M.; Alamoudi, Saeed O.; AL-Alawi, Talal I.; Alkhateeb, Anas A.; Albuqayli, Adnan S.; Alothmany, Hamzah N. (Frontiers in Public Health, 2024)
IntroductionPrevious studies have shown that mental health issues such as depression and anxiety are on the rise globally, particularly among university students. The aim of this study is to assess the prevalence of depressive and anxiety symptoms among university students, and the associated potential risk factors, in Jeddah, Saudi Arabia.MethodsA cross-sectional questionnaire study was conducted in a sample of 728 students who anonymously completed three sets of questionnaires: a sociodemographic and lifestyle information questionnaire, the Patient Health Questionnaire-9 (PHQ-9) to screen for depressive symptoms and the Generalized Anxiety Disorder-7 (GAD-7) scale to screen for anxiety symptoms.ResultsIn a survey of 728 students, 81.5% reported depression and 63.6% anxiety, with no difference between medical and non-medical majors. Regular exercise, a history of psychological disorders, a diagnosis of chronic illness, and the use of antidepressant medications were significant indicators of depression. Significant anxiety markers included female gender, a diagnosis of chronic illness, a history of psychological disorders, the use of antidepressant medications, and smoking. Surprisingly, we did not observe any significant differences between the prevalence of depression or anxiety symptoms and common risk predictors, such as poor academic performance, low family income, and year of study.ConclusionDepression and anxiety had a high prevalence among undergraduates, regardless of their field of study; therefore, we recommend the implementation and expansion of community-based mental health prevention programs and mentorship programs. Universities with counseling programs should identify and eliminate factors that contribute to depression and anxiety.